HISTOLOGICAL CHANGES IN THE TESTI OF PURE INBRED SWISS MICE INDUCED BY PERMETHRIN INSECTICIDE - Balash, Khawla Jassim (The Iraqi Journal of Veterinary Medicine, 2000)
Permethrin, is a synthetic insecticide of appreciably low mammalian toxicity, it is especially useful for household purposes. This work aimed to study the gonadotoxic effect of this insecticide in Swiss mice, using two oral doses of 2000 and 3000 mg/kg b. w. for 30 days. The daily dose was 1.66 mg/kg and 2.5 mg/kg of active ingredient of permethrin for group | and group || respectively. The effect was determined by counting the percentage of damaged seminiferous tubules, their average diameter, and the spermatogenesis rate, also the changes in body weight and in testes-to-body weight ratio. Results showed that the insecticide caused significant reduction in body weight, increase in testes weight, as well as testes-to-body weight ratio, seminiferous tubules in treated animals were found to increase in diameter showing low degrees of damage. Nevertheless, spermatogenic activity was almost normal but in descending order, and Leydig cells remained unaffected. It was concluded that permethrin, has a slight gonadotoxic effect at the doses used which may not really affect the fertility of animals at the doses used.